Pengaruh Kecerdasan Matematis-Logis dan Kecerdasan Intrapersonal Terhadap Hasil Belajar Matematika Siswa - Amrida Rahmadani; Rusdi Rusdi; Risnawita Risnawita; Tasnim Rahmat (Departement of Mathematics Education, 2023)
This research is based on the results of interviews conducted at the school, which revealed that students' mathematics learning outcomes are relatively low, possibly due to the influence of mathematical-logical intelligence and intrapersonal intelligence. This study is a correlational study using the ex post facto method. The aim of the research is to determine the influence of mathematical-logical intelligence and intrapersonal intelligence on students' mathematics learning outcomes in Grade IX of SMPN 1 Ampek Angkek for the academic year 2022/2023, both partially and simultaneously. The population of this study consists of 183 Grade IX students at SMPN 1 Ampek Angkek. The research sample consists of 32 students selected using simple random sampling technique. The data collection techniques used in this study were tests, questionnaires, and documentation. The data were analyzed using simple linear regression and multiple linear regression. The results of the study showed that: (1) Mathematical-logical intelligence has a positive influence on mathematics learning outcomes with a contribution of 19.45%, (2) Intrapersonal intelligence has a positive influence on mathematics learning outcomes with a contribution of 13.32%, and (3) Mathematical-logical intelligence and intrapersonal intelligence have a positive influence on mathematics learning outcomes with a contribution of 34.57%. Thus, it can be concluded that mathematical-logical intelligence and intrapersonal intelligence have a positive influence on students' mathematics learning outcomes in Grade IX of SMPN 1 Ampek Angkek for the academic year 2022/2023, both partially and simultaneously.